Pediatric Ophthalmology, Neuro-Ophthalmology, Genetics Strabismus - New Concepts in Pathophysiology, Diagnosis, and Treatment - Lorenz, Birgit; Brodsky, Michael C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The 8 recurring volumes of the "Essentials in Ophthalmology" series cover the most recent developments in one of eight subspecialties in Ophthalmology. With four volumes published per year, each subspecialty is newly visited every 24 months, with a distinct focus on recent developments. By bridging the gap between original research and medical textbooks, the transfer of this developing knowledge into daily practice is greatly enhanced.
Epidemiology of Pediatric Strabismus -- Changes in Strabismus Over Time: The Roles of Vergence Tonus and Muscle Length Adaptation -- A Dissociated Pathogenesis for Infantile Esotropia -- The Monofixation Syndrome: New Considerations on Pathophysiology -- Visual Cortex Mechanisms of Strabismus: Development and Maldevelopment -- Neuroanatomical Strabismus -- Congenital Cranial Dysinnervation Disorders: Facts and Perspectives to Understand Ocular Motility Disorders -- The Value of Screening for Amblyopia Revisited -- The Brückner Test Revisited -- Amblyopia Treatment 2009 -- Best Age for Surgery for Infantile Esotropia: Lessons from the Early vs. Late Infantile Strabismus Surgery Study -- Management of Congenital Nystagmus with and without Strabismus -- Surgical Management of Dissociated Deviations -- Surgical Implications of the Superior Oblique Frenulum -- Pearls and Pitfalls in Surgical Management of Paralytic Strabismus -- Modern Treatment Concepts in Graves Disease.
Keywords: Medicine; Neurology; Ophthalmology; Pediatrics; Medicine & Public Health; Ophthalmology; Pediatrics; Neurology